Improved Bathymetric Prediction Using Geological Information: SYNBATH. Issue 2 (3rd February 2022) - Sandwell, David T.; Goff, John A.; Gevorgian, Julie; Harper, Hugh; Kim, Seung‐Sep; Yu, Yao; Tozer, Brook; Wessel, Paul; Smith, Walter H. F.
Abstract: To date, ∼20% of the ocean floor has been surveyed by ships at a spatial resolution of 400 m or better. The remaining 80% has depth predicted from satellite altimeter‐derived gravity measurements at a relatively low resolution. There are many remote ocean areas in the southern hemisphere that will not be completely mapped at 400 m resolution during this decade. This study is focused on the development of synthetic bathymetry to fill the gaps. There are two types of seafloor features that are not typically well resolved by satellite gravity; abyssal hills and small seamounts (<2.5 km tall). We generate synthetic realizations of abyssal hills by combining the measured statistical properties of mapped abyssal hills with regional geology including fossil spreading rate/orientation, rms height from satellite gravity, and sediment thickness. With recent improvements in accuracy and resolution, it is now possible to detect all seamounts taller than about 800 m in satellite‐derived gravity and their location can be determined to an accuracy of better than 1 km. However, the width of the gravity anomaly is much greater than the actual width of the seamount so the seamount predicted from gravity will underestimate the true seamount height and overestimate its base dimension. In this study, we use the amplitude of the vertical gravity gradient (VGG) to estimate the mass of the seamount and then use their characteristic shape, based on well‐surveyed seamounts, to replace the smooth‐predicted seamount with a seamount having a more realistic shape. Plain Language Summary: The floor of the deep ocean remains as the last uncharted frontier in the inner solar system. The deep seawater (>1, 000 m) prevent any type of exploration from conventional satellite remote sensing. Echosounders aboard large vessels have mapped about 20% of the seafloor, however, vast areas in the southern hemisphere will not be mapped in our lifetimes. The deep ocean floor has more than 90% of the active volcanoes; hydrothermal circulation of seawater through the crust of the seafloor spreading ridges replenishes the nutrients needed for life on Earth. This study is an effort to fill the large gaps in seafloor coverage by creating a synthetic abyssal hill fabric using geological information such as the age of the seafloor, the spreading rate and direction when it formed, and the thickness of the sediments covering the original topography. In addition, we use the latest satellite‐derived gravity to estimate the locations and shapes of about 20, 000 uncharted seamounts. The combination of mapped (20%) and synthetic (80%) topography is useful for modeling ocean circulation and ocean tides although it may give a false impression that 100% of the seafloor has been mapped. Key Points: ∼20% of the ocean floor topography has been surveyed by ships, the remaining 80% is predicted by satellite altimetry We increased the resolution of the predicted depth using spectral properties of abyssal hills and the characteristic shapes of seamounts We estimate the height and radius of 19, 000 uncharted seamounts